Entry and exit barriers and their impact on industry performance -A case study of the mobile phone service industry in Algeria - Adil, Argabi; Amar, Taleb; Samir, Salhaoui (The journal of contemporary issues in business and government, 2023)
Through this study, we have tried to shed light on a very important topic, which is the barriers to entry and exit to and from the industry and its impact on its performance, and this is through a case study of a very important industry in Algeria, which is the mobile service industry, using the descriptive approach Analysis through the case study technique, the study found that there are high entry and exit barriers within this industry, whether natural entry barriers, which were represented in both economies of scale Large, capital requirements, technological development, and strategic entry barriers, which were represented in both price limits and access to distribution channels, legal entry barriers, which were represented by the intervention of the Postal and Telecommunications Regulatory Authority through laws that regulate competition within the industry, in addition to exit obstacles, which were the difficulty of recovering large investments and the legal penalty resulting from the assignment of a license to the country. All this has greatly affected the development of the industry's performance, as this industry is considered among the most developed industries in Algeria, whether through the number of subscribers, which reached more than 47 million subscribers in 2018, or through the industry's turnover, which reached its largest value in 2016, estimated at 349 billion Algerian dinars, or through the industry's net profits, which amounted to 104.22 billion Algerian dinars in the year. 2017.